The Economic Imperative: How Telemedicine is Reshaping Rural Healthcare Finance - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The Economic Imperative: How Telemedicine is Reshaping Rural Healthcare Finance The healthcare landscape in rural areas faces a persistent and critical ...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Patient Care; Clinical Decision Support